Analisis Usulan Undang-Undang oleh Presiden Prabowo Subianto Tahun 2024–2025 Perspektif Siyāsah Dustūriyyah - Fauzan Naufal; Syafruddin Syam (CV Global Research Publication, 2026)
This study aims to analyze the considerations underlying the Government of President Prabowo Subianto in proposing several laws during the 2024–2025 legislative period and to examine these laws from the perspective of Fikih Siyāsah (Islamic constitutional jurisprudence). This research employs a normative juridical method using statutory and conceptual approaches. The data were collected through library research by examining primary, secondary, and tertiary legal materials. The results indicate that the proposed laws were intended to strengthen national defense, improve the governance of State-Owned Enterprises (SOEs), reform governmental institutions, and support the implementation of the National Long-Term Development Plan toward Indonesia Emas 2045. However, several provisions have generated legal and constitutional debates. Law Number 3 of 2025 concerning the Indonesian National Armed Forces (TNI) has raised concerns regarding the expansion of military involvement in civilian institutions. Law Number 1 of 2025 concerning State-Owned Enterprises introduces reforms in SOE governance through the establishment of the Daya Anagata Nusantara Investment Management Agency (Danantara). Law Number 61 of 2024 concerning State Ministries expands the President's authority in coordinating government institutions, while Law Number 59 of 2024 concerning the National Long-Term Development Plan provides the legal framework for implementing the government's long-term development agenda. From the perspective of Fikih Siyāsah, these legislative policies should be implemented based on the principles of justice (al-'adālah), trustworthiness (al-amānah), consultation (al-syūrā), and public interest (al-maṣlaḥah) to ensure constitutional governance that is accountable and oriented toward the welfare of society.